Fenomena Pengelolaan Kelas Pada Pembelajaran Di Sekolah Dasar - Ardiansyah, Tomy; Setiono, Panut (JURIDIKDAS, 2024)
This research aims to describe the phenomenon of classroom management skills in learning at SD Negeri 11 Kota Bengkulu. This study is a descriptive qualitative research. The subjects of this research are teachers from class IIA and IVA. The results of this research indicate that teachers are quite effective in implementing preventive classroom management skills, such as being attentive to students, providing clear instructions, observing closely, approaching students, making statements, reacting to disruptive behavior, giving admonishments, providing reinforcement, and demanding responsibility. On the other hand, the skills that are considered punitive include giving punishments and addressing problematic student behaviors. However, there are still areas that need improvement in certain activities. For example, in terms of being attentive to students and approaching them, teachers have weaknesses in simultaneously observing the overall activities of the students. Furthermore, in activities that demand responsibility from students, teachers pay little attention to the culture of queuing in cultivating students' sense of responsibility.